Conducting Polymers for Neural Prosthetic and Neural Interface Applications. (28th September 2015) - Green, Rylie; Abidian, Mohammad Reza
Abstract : Neural‐interfacing devices are an artificial mechanism for restoring or supplementing the function of the nervous system, lost as a result of injury or disease. Conducting polymers (CPs) are gaining significant attention due to their capacity to meet the performance criteria of a number of neuronal therapies including recording and stimulating neural activity, the regeneration of neural tissue and the delivery of bioactive molecules for mediating device–tissue interactions. CPs form a flexible platform technology that enables the development of tailored materials for a range of neuronal diagnostic and treatment therapies. In this review, the application of CPs for neural prostheses and other neural interfacing devices is discussed, with a specific focus on neural recording, neural stimulation, neural regeneration, and therapeutic drug delivery. Abstract : Neural interfaces are artificial extensions that restore or supplement the function of the nervous system that is lost after injury or disease. Conducting polymers are gaining significant attention due to their capacity to meet the performance criteria of a number of neuronal therapies, including recording and stimulating neural activity, the regeneration of neural tissue, and the delivery of bioactive molecules for controlling neural‐cell behavior. This flexible platform technology enables the development of tailored materials for a range of neuronal diagnostic and treatment therapies.